Party Membership and State Jobs in Urban China - Yuanyuan Ma; Patrick Paul Walsh (Institute for the Study of Labor (IZA), 2013)
The dual-track approach for transition would have to be facilitated by an endogenous movement of workers away from the state into private jobs. Yet, using the Chinese Household Income Project Series (CHIPs) data for the year 2002, we document preferences and premiums for state jobs in urban China over private jobs. The state sector attracted the best workers in more favorable industries and regions and offered higher earning premiums. In addition, family party membership is found to be instrumental in allocating workers into state jobs which explains a good deal of the earnings differentials in terms of an endogenous state premium.
Keywords: J42; J62; O15; P23; R23; 330; labor mobility; earnings differentials; party networks; state jobs; urban China